Personal Data Protection Through Law Number 27 Of 2022: Challenges Of Cybercrime in The Era of Globalization and Digital - Utomo, Setyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research was compiled based on the urgency of massive technological and information developments in Indonesia. Due to this development, it is also accompanied by negative impacts in the form of cybercrime targeting people's personal data. The implementation of the law must be in accordance with the reality of the development of the times. The formulation of the problem taken and discussed in this study is how the development of personal data protection through Law Number 27 of 2022 and how urgent Law Number 27 of 2022 is in meeting the demands of the community for personal data protection. The method used is normative juridical which uses primary data. The search for literature sources uses library studies. The results of this study are that the Government of the Republic of Indonesia through Law Number 27 of 2022 guarantees the right to privacy and personal data of citizens as one of the protections of human rights. Furthermore, this personal data protection law becomes a law that aligns Indonesian personal data protection regulations with international standards. Sanctions for violations of personal data protection provisions are also stated more firmly in this law